Extended uterine receptivity for blastocyst implantation and full‐term fetal development in mice with vitrified–warmed ovarian tissue autotransplantation - Matsumoto, Hiromichi (Reprod Med Biol, 2012)
PURPOSE: Our previous study demonstrated that vitrified–warmed ovarian tissue autotransplantation (VOAT) into estrus cycle‐ceased ovariectomized mice restored fertility to achieve full‐term fetal development for transferred embryos, while less steroidogenesis in the corpus luteum was observed in VOAT mice. It has been reported that the window of uterine receptivity for blastocyst implantation is extended at lower estrogen levels. Therefore, we hypothesized that duration of the window in VOAT mice could be extended. METHODS: Blastocysts were transferred into VOAT mice on day 5 of pseudopregnancy. Immunohistochemical analysis was performed to examine the potential in VOAT ovarian tissues. RESULTS: The rate of live birth pups from embryos transferred on day 5 of pseudopregnant VOAT mice was not different from that of embryos transferred on day 4 of pseudopregnancy in VOAT mice, while embryo transfer on day 5 into intact mice showed no pregnancy. Immunohistochemical analysis of the corpus luteum of day 8 pseudopregnant VOAT mice with uteri having decidualization induced on day 5 showed less steroidogenesis and blood vessel formation as compared to intact mice. CONCLUSIONS: Uterine receptivity was extended in VOAT mice. Less steroidogenesis and blood vessel formation in the transferred ovarian tissues may be associated with the extended uterine receptivity.